Drain / Muhammad Asri Azuddin and Mohamad Zaidi Sulaiman - Azuddin, Muhammad Asri; Sulaiman, Mohamad Zaidi (2022)
Remembering the year 2019, when the first case of COVID-19 was found in Malaysia, was the starting point where the emotional decline at every level of society was rocked by the anxiety of thinking about how to continue living. This anxiety was caused by the fear of not knowing how to continue living. It is also made worse by the instability of political institutions and a government that is unstable, both of which contribute to the instability of the economy in the country and contribute to the mental health problems of the people. This is because the majority of people begin to lose their source of income, which in turn leads to a variety of other problems.